Global prevalence of Cryptosporidium spp. in cats: A systematic review and meta-analysis. (July 2021) - Taghipour, Ali; Khazaei, Sasan; Ghodsian, Sahar; Shajarizadeh, Mina; Olfatifar, Meysam; Foroutan, Masoud; Eslahi, Aida Vafae; Tsiami, Amalia; Badri, Milad; Karanis, Panagiotis
Abstract: The One-Health approach highlights that the health of human populations is closely connected to the health of animals and their shared environment. Cryptosporidiosis is an opportunistic zoonotic disease considering as global public health concern. Cats are considered as one of potential host for transmitting the Cryptosporidium spp. infection to humans. A random-effects meta-analysis model was used to estimate the overall and the subgroup-pooled prevalence of Cryptosporidium spp. across studies, and the variance between studies (heterogeneity) were quantified by I 2 index. Eighty articles (including 92 datasets), from 29 countries met eligibility criteria for analysis. The pooled global prevalence (95% CI) of Cryptosporidium spp. in cats was 6% (4–8%), being highest in Africa 14% (0–91%) and lowest in South and Central America 4% (3–7%) countries. Considering the detection methods, the pooled prevalence was estimated to be 26% (1–67%) using serological detection methods, 6% (3–10%) using coproantigen detection methods, 5% (3–7%) using molecular detection methods, and 4% (3–7%) using microscopic detection methods. The highest prevalence of Cryptosporidium spp. was found in stray cats 10% (5–17%), while pet (domestic) cats 4% (3–7%) had the lowest prevalence. These results emphasize the role of cats as reservoir hosts for human-infecting Cryptosporidium spp. Prevention and control of this zoonosis in cats should receive greater attention by health officials and health policymakers, especially in countries where prevalence are highest. Highlights: Cats are considered as one of potential host for transmitting the Cryptosporidium infection to humans. The pooled global prevalence (95% CI) of Cryptosporidium infection in cats was 6% (4–8%). The highest prevalence of Cryptosporidium was found in stray cats 10% (5–17%), while pet (domestic) cats 4% (3–7%) had the lowest prevalence. Considering the molecular methods, C. felis was the most prevalent species/genotype, followed by C. parvum and Cryptosporidium rat genotype III.